TIPOLOGIAS HABITACIONAIS DE DENSIDADE INTERMEDIÁRIA - Moretti, Ricardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The building density control is one of the tension points in the public action of territory planning and is strategic in the current context of strong pressure from the real estate market for solutions that maximize profitability. The hypothesis of this paper is that in big cities the intermediate population densities (between 50 and 150 square meters of land per housing unit share) constitute a balance between public and private interests and should be encouraged as a public policy. Some types of production of the city leading to intermediate density ranges are analyzed and compared to two formal market solutions: high rise residential buildings and isolated dwelling units in low density closed neighborhoods. The results confirmed the importance of public policies to stimulate intermediate density solutions, aiming streamlining costs, local economic development and improvements in the quality of the urban environment.